Implementation of Autoregresssive Integrated Moving Average (ARIMA) on Forecasting the Number of Positive Cases of Covid-19 in North Sumatra on September 2021: Implementasi Autoregresssive Integrated Moving Average (ARIMA) Pada Peramalan Jumlah Kasus Positif Covid-19 Sumatera Utara Pada September 2021 - Zahedi; Laia, Herlina Fransiska (Talenta Publisher, 2022)
North Sumatra is one of the provinces in Indonesia with a high number of positive cases of Covid-19 so that North Sumatra has been in the red and yellow zone for several months. The increasing number of positive cases can have an impact on various aspects of people's lives. To do optimal mitigation, forecasting is necessary, which is a technique to estimate a value in the future by paying attention to past data and current data. One method that can be used is the ARIMA method. The data used is daily data from May to August 2021 obtained from the official website of the covid19.go.id. The ARIMA model obtained from this study is the ARIMA(1,1,0) model with MAE, MAPE and MSE values of 453,175203, 3,312754324, and 6161032,938, respectively. Forecast results for September show a daily increase so it is expected that the government will make efforts to prevent this.